PENGEMBANGAN PEMBELAJARAN US}U>L AL-FIQH BERBASIS KOMPETENSI PADA MADRASAH ALIYAH KEAGAMAAN DI PONOROGO - Basuki Basuki (Muslim Heritage, 2018)
Abstract: This article aims to explain the objectives, materials, strategies, and evaluations that have been formulated from us}u>l al-fiqh learning in Religious Madrasah Aliyah (MAK) in Islamic boarding schools in Ponorogo district, especially at MAK Pondok "Hudatul Muna" Islamic Boarding School Jenes Ponorogo, MAK "Al-Islam" Islamic Boarding School Joresan Mlarak Ponorogo, and MAK "Darul Huda" Islamic Boarding School Mayak Ponorogo. This study employed qualitative approach and researchers themselves are key instruments, while other instruments are supporting instruments. This type of research is a multi-case study (multi-case studies). The findings showed that the teaching and learning of  us}u>l al-Fiqh in MAK in the Islamic boarding school at Ponorogo are in the following: First, the learning objectives developed are by using 3 eclectic approaches, namely subject-academic, humanistic, and technological approaches. However, it has not been developed using the reconstruction-social approach. Second, the structure of learning material is included in the structure of subject matter in an integral system (manhaj al-mawa> dd al-mutarabit} ah), which cannot be separated from other subjects, such as al-Qur'a> n, al-Hadith, al -Tafsi> r, Ulu> m al-Qur'an> n, Ulu> m al-Hadi> th, al-Fiqh, 'Ilm al-Nahw, and' Ilm al-S} arf. Third, learning activities have two main functions, namely [1] the task as profession, namely educating, teaching and training; [2] the task of humanity, namely being a supplementary parent, and self-transformation. Third, the learning evaluation system is one of the factual ways to see the basic competencies and abilities of students in mastering the material individually.Abstrak: Artikel ini bertujuan mendeskripsikan dan menjelaskan tujuan, materi-materi, strategi-strategi, dan evaluasi yang telah dirumuskan dari pembelajaran us}u>l al-fiqh pada Madrasah Aliyah Keagamaan (MAK) di lingkungan pondok pesantren di kabupaten Ponorogo, khususnya di MAK Pondok Pesantren ”Hudatul Muna” Jenes Ponorogo, MAK Pondok Pesantren ”Al-Islam” Joresan Mlarak Ponorogo, dan MAK Pondok Pesantren ”Darul Huda” Mayak Ponorogo. Penelitian ini menggunakan pendekatan kualitatif, latar alami (natural setting) sebagai sumber data langsung dan peneliti sendiri merupakan instrumen kunci, sedangkan instrumen lain sebagai instrumen penunjang. Jenis penelitian ini adalah studi multi-kasus (multi-case studies). Dari hasil penelitian tentang pembelajaran  us}u>l al-Fiqh pada MAK di lingkungan Pondok Pesantren kabupaten Ponorogo ini, temuan peneliti yaitu: Pertama, Tujuan pembelajaran yang dikembangkan adalah dengan menggunakan 3 pendekatan secara eklektik, yaitu subyek-akademis, humanistis, dan teknologis. Dan belum dikembangkan dengan menggunakan pendekatan rekonstruksi-sosial. Kedua, Struktur materi pembelajaran termasuk dalam struktur materi pelajaran dengan sistem integral  (manhaj al-mawa>dd al-mutarabit}ah), yakni tidak bisa dilepaskan dari mata pelajaran lain, seperti al-Qur'a>n, al-Hadith, al-Tafsi>r, Ulu>m al-Qur'a>n, Ulu>m al-Hadi>th, al-Fiqh, 'Ilm al-Nahw, dan 'Ilm al-S}arf. Ketiga, Kegiatan pembelajaran  mempunyai dua fungsi utama, yaitu [1] tugas profesi, yakni mendidik, mengajar dan melatih; [2] tugas kemanusiaan, yakni menjadi orangtua kedua, dan transformasi diri. Ketiga, Sistem evaluasi pembelajaran adalah merupakan salah satu cara yang tepat untuk melihat standar kompetensi dan kemampuan dasar santri dalam penguasaan materi secara individual.